Reference Model-Based Backstepping Control of Semi-Active Suspension for Vehicles Equipped with Non-Pneumatic Wheels - Jie Chen; Wei Liu; Renkai Ding; Dong Sun; Ruochen Wang (Machines)
In view of the deterioration of vehicle dynamic performance caused by the increased radial stiffness of a non-pneumatic wheel and its nonlinearity, a semi-active suspension error tracking backstepping control strategy based on the model reference method is proposed. Firstly, the segmental linearization of the nonlinear stiffness of the non-pneumatic wheels is carried out, and a quarter-vehicle system model integrating the non-pneumatic wheel and the semi-active suspension is established. Subsequently, a model reference system based on the <semantics>H∞</semantics> control theory is designed. On this basis, a semi-active suspension error tracking backstepping controller based on the reference model is developed. Finally, comparative dynamics simulations are carried out to verify the effectiveness of the controller. The results indicate that the designed controller exhibits a superior control effect compared with the existing controllers. Specifically, the proposed control method reduces the root-mean-square (RMS) value of sprung mass acceleration by 20.0% under random road excitation compared to passive suspension while ensuring system constraints, and reduces the peak-to-peak (P-P) values of sprung mass acceleration and dynamic wheel load by 60.6% and 42.5% under bumpy road excitation, respectively.